The response of Saturn's dawn field-aligned currents to magnetospheric and ring current conditions during Cassini's proximal orbits: evidence for a Region 2 response at Saturn - Hunt,GJ; Provan,G; Bradley,TJ; Cowley,SWH; Dougherty,MK; Roussos,E (Journal of Geophysical Research: Space Physics, 2022)
Cassini's 2017 proximal orbits provided the opportunity to examine the auroral field-aligned currents in the northern hemisphere dawn sector in relation to wider magnetospheric conditions. We combine three recent studies to examine the response of the dawn region auroral field-aligned currents and the azimuthal ring currents to compressions and expansions of the Saturnian magnetosphere. For compressions of Saturn's magnetosphere resulting in tail reconnection, the currents within the downward current sheet, located equatorward of the main auroral oval, increases in strength with increasing total ring current and location of the peak downwards current moves inwards toward Saturn. While the inverse relation occurs during intervals of quiet or expanded magnetospheric conditions. During compression events there is an increase in the energetic particle intensities, in particular in the protons (35–506 keV), within the downward current region. This current system is akin to an Earth-like “region 2” field aligned current within Saturn's magnetosphere, with tail reconnection occurring when the magnetosphere is compressed resulting in a partial nightside ring current closed by a downward current near to dawn. Within the upward current sheet, mapping to Saturn's main auroral oval, both non-rotating subcorotating current and the rotating Planetary Period Oscillations (PPOs) currents flow. The upward current is strongly modulated by the PPOs but also increases in strength, with enhanced high-energy protons, during intervals of magnetospheric compressions and tail reconnection. We conclude that the enhanced plasma injected into the midnight-dawn sector during tail reconnection events results in an enhanced subcorotation current system.